A light-controlled biocatalytic system for precise regulation of enzymatic decarboxylation. Issue 11 (18th May 2022) - Cheng, Feng; Wu, Dong-Yang; Liang, Xi-Hang; Wang, Cheng-Jiao; Weng, Jia-Qi; Zou, Shu-Ping; Xu, Jian-Miao; Xue, Ya-Ping; Zheng, Yu-Guo
Abstract : A light-controlled biocatalytic one-pot system is developed, which enables precise regulation of gene expression and photocatalysis by illumination and yields high conversion and stereoselectivity. Abstract : Precise control of a biocatalytic system is highly important but remains a major challenge. Herein, we developed a light-controlled enzyme production-biocatalysis one-pot system by combination of photocatalysis and photogenetic-regulated enzyme production. As proof-of-principle, a photoenzyme in an Escherichia coli -based biocatalyst was produced and restored by gene expression in the dark for decarboxylation under illumination. The kinetic resolution of racemic phosphinothricin with an intermittent illumination model displayed higher conversion (49%) and excellent stereoselectivity (ee = 98%), compared to a continuous illumination model (conv. = 44%; ee = 71%).